PENGEMBANGAN INSTRUMEN KECERDASAN EMOSIONAL - SANTI LISNAWATI (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2011)
The purpose of this research is to develop an instrument to measure emotional intelligence of high school students. The sample of this research was taken using multi stage random sampling technique. The instrument was developed using Thurstone scale, consisting of 90 items. A panel of judges was involved to review and select the items and based on the rational judgment; scores of scale (S), interquartile range (Q) were calculated, giving 45 items chosen. The instrument was tried out to 480 high school students in Bogor. Construct validity was calculated by using factor analysis. The result indicated that 5 factors were extracted from the data obtained by using exploratory method Principal Component Analysis (PCA), which is in accordance with the theoretical estimated factors; the confirmatory method used is the maximum likelihood (ML) to test the goodness of fit of the factors. The obtained index of test of the 5 factors is 1108,269. Therefore, it can be convinced that the correlation model of the five factors is valid. Alpha reliability is used to determine the reliability of the instrument (Î± = 0,783). It can be concluded that the questionnaire measuring emotional intelligence has appropriate construct validity an internal consistency. Further tryout is still needed to standardize the instrument.